Peran Fotografi Jurnalistik pada Era Digital - Reza Febrio Fajar Pangestu (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. In today's digital era, journalistic photography is an important visual-based communication tool. Journalistic photography is a branch of a large group in the field of photography, apart from art photography and commercial photography. As a field of art, photography journalism certainly has its aesthetic concept, even if the aesthetic concept is closely related to